Serum Levels of Joining Chain-Containing IgA1 Are Not Elevated in Patients with IgA Nephropathy. (2nd July 2019) - Li, Guanhong; Wang, Xiaoyan; Yang, Zhe; Zhao, Qing; Wen, Yubing; Li, Xuemei; Gao, Ruitong
Abstract : Background . It has been suggested that mesangial IgA deposits are dimeric or polymeric in IgA nephropathy (IgAN). However, evidence concerning the molecular form of serum IgA in IgAN is controversial. And there is no direct evidence that the serum levels of joining chain- (J chain-) containing IgA (J-IgA) are elevated in IgAN. In this study, we aimed to measure serum J-IgA and glomerular J chain deposition with anti-J chain monoclonal antibody in IgAN. Methods . BALB/c mice were immunized with human J chain-GST recombinant peptide to obtain anti-J chain monoclonal antibody. The levels of serum total IgA and J-IgA were measured by sandwich enzyme-linked immunosorbent assay in 115 patients with IgAN and 117 healthy volunteers. J chain deposition in kidney specimens was analyzed by immunohistochemistry staining. Results . Serum levels of total IgA1 were elevated in IgAN patients compared to healthy subjects. However, serum levels of IgA, J-IgA, and J chain-containing IgA1 (J-IgA1), the J-IgA to total IgA ratio, and the J-IgA1 to total IgA1 ratio were not significantly different between IgAN patients and healthy subjects. Western blot analysis and gel filtration analysis using purified IgA1 also showed that the proportion of J chain-containing polymeric IgA1 was lower in IgAN patients compared to healthy subjects. No correlation was found between serum J-IgA or J-IgA1 and clinical features in IgAN. Immunohistochemistry analysis showed that glomerular J chain was positive in 12 IgAN patients (57.1%). The values of the J-IgA to IgA ratio and J-IgA1 to IgA ratio were significantly higher in IgAN patients with glomerular J chain deposition than those without. However, the serum levels of J-IgA and J-IgA1 and the J-IgA1 to IgA1 ratio were not significantly higher in two subgroups. Conclusions . Although serum levels of total IgA1 were elevated in IgAN, the serum levels of J-IgA1 were not elevated. And serum J-IgA, serum J-IgA1, and J chain deposition were not correlated with disease severity in IgAN.